Arah dan Perkembangan Liposome Drugs Delivery Systems - Jufri, Mahdi (UI Scholars Hub, 2004)
Since the dicovery of liposome or lipid vesicles derived from self limiting enclosed lipid bilayer upon hydration, liposome drug delivery systems have played a significant role in formulation of potent drugs to improve therapeutics. Currenlty most of these liposome formulation are designed to reduced toxicity and to some extent increase accumulation at the target site(s) in a the number of clinical application. The current pharmaceutical preparations of liposome based therapeutics stem from our understanding of lipid drug interactions and the liposome disposition mechanism including the inhibition of rapid clearance of liposome by controlling size , charge and surface hydration.